The role of food quality in clonal succession in Daphnia: an experimental test - Brzeziński, Tomasz (Springer-Verlag, 2010)
A high genetic variation and recurrent changes in the genetic structure have been found in many pelagic populations. However, evidence that directly links these changes to differences in the ecological performance of particular genotypes is scarce. We hypothesized that within Daphnia, the specialization of clones occurring in a particular season to the food quality specific for that time of the year is responsible for the observed changes in the genetic structure of a population. This hypothesis was tested by comparing the fitness of spring and summer clones of the Daphnia longispina group, given food of biochemical quality relevant to these seasons. We identified significant intraspecific differences between clones of Daphnia that are specific for particular seasons, but there was no evidence that clones are adapted to the food quality available at the respective times of year. Summer clones reproduce at smaller size, and have a lower juvenile specific growth rate as compared to spring clones, irrespective of food quality. Spring clones invest more energy in somatic growth at the cost of reproduction, whereas summer clones invest more energy in reproduction at the cost of somatic growth. On the basis of the observed differences between spring and summer clones in their patterns of energy allocation, we suggest that other factors, most likely predation, are the major forces driving phenotypic and genetic diversity in the investigated Daphnia population of a large lake.